Senegal country brief - Kampman, Haile; Park, Seollee; Rawat, Rahul; Becquey, Elodie; Zongrone, Amanda (Transform Nutrition, 2016)
Senegal has made impressive improvements in nutrition in recent years and is often seen as a success story for stunting reduction, though there are a number of important challenges remaining. The hope is that by identifying the factors which contributed to this positive change, the nutrition community can learn from the successes and challenges of Senegal’s story of change in nutrition. This brief summarises the findings from a research study – Stories of Change in Nutrition in Senegal – the aim of this study is to develop a story which helps to explain the interrelated factors that contributed to Senegal’s reduction in undernutrition. The hope is that these findings will help to contribute to wider impacts in terms of political commitment and policy coherence for nutrition.